Gender and age-related cell compositional differences in C57BL/6 murine adipose tissue stromal vascular fraction. (3rd July 2018) - Frazier, Trivia; Lee, Stephen; Bowles, Annie; Semon, Julie; Bunnell, Bruce; Wu, Xiying; Gimble, Jeffrey
ABSTRACT: Adipose tissue is now recognized as a functional organ that contains cellular heterogeneity and diversity within anatomical depots. The stromal vascular fraction (SVF) of adipose contains endothelial progenitors, fibroblasts, lymphocytes, monocyte/macrophages, pericytes, pre-adipocytes, and stromal/stem cells, among others. In recent years, there has been a growing appreciation of the influence of age and gender in the field of stem cell biology. Yet few studies have evaluated the influence of biological age or sex on either SVF cell heterogeneity or immunophenotype. To address this issue, the current study has compared the flow cytometric characteristics between murine SVF of inguinal (iWAT), epidydimal (eWAT), and brown (BAT) adipose tissue of male and female, as well as young (6–8 week) and middle-aged (8–12 month) male C57BL/6 mice. Murine gender comparisons revealed male iWAT expressed higher percentages of leukocyte and CD34 + ASC-like sub-populations than female iWAT. Murine age comparisons revealed younger male iWAT, eWAT, and BAT SVF all contained a significantly higher percentage of pre-adipocytes, HSC-like cells, CD25 −, and FoxP3 + T-regulatory cells compared to SVF from middle-aged male mice. These findings highlight the potential contribution of biological variables on adipose-derived cell applications and experimental outcomes.